Molecular Mechanisms for cAMP-Mediated Immunoregulation in T cells – Role of Anchored Protein Kinase A Signaling Units - Wehbi, Vanessa L.; Taskén, Kjetil (Frontiers in Immunology, 2016)
The cyclic AMP/protein kinase A (cAMP/PKA) pathway is one of the most common and versatile signal pathways in eukaryotic cells. A kinase anchoring proteins (AKAPs) target PKA to specific substrates and distinct subcellular compartments providing spatial and temporal specificity for mediation of biological effects channeled through the cAMP/PKA pathway. In the immune system cAMP is a potent negative regulator of T cell receptor (TCR)-mediated activation of effector T cells (Teff) acting through a proximal PKA/Csk/Lck pathway anchored via a scaffold consisting of the AKAP Ezrin holding PKA, the linker protein EBP50 and the anchoring protein PAG holding Csk. As PKA activates Csk and Csk inhibits Lck this pathway in response to cAMP shuts down proximal T cell activation. This immunomodulating pathway in Teff mediates clinically important responses to regulatory T cell (Treg) suppression and inflammatory mediators such as prostaglandins, adrenergic stimuli, adenosine and a number of other ligands. A major inducer of T cell cAMP levels is prostaglandin E2 (PGE2) acting through EP2 and EP4 prostanoid receptors. PGE2 plays a crucial role in the normal physiological control of immune homeostasis as well as in inflammation and cancer immune evasion. Peripherally induced regulatory T cells express COX-2, secrete prostaglandin E2 (PGE2) and elicit the immunosuppressive cAMP pathway in effector T cells as one tumor immune evasion mechanism. Moreover, a cAMP increase can also be induced by indirect mechanisms such as intercellular transfer between T cells. Indeed, Treg, known to have elevated levels of intracellular cAMP, may mediate their suppressive function by transferring cAMP to Teff through gap junctions, which we speculate could also be regulated by PKA/AKAP complexes. In this review we present an updated overview on the influence of cAMP-mediated immunoregulatory mechanisms acting through localized cAMP signaling and the therapeutical increasing prospects of AKAPs disruptors in T cell immune function.